Onieric travels through history. "Where have you been, Robert?" by Hans Magnus Enzensberger - MUELA BERMEJO, Diana (Ondina - Ondine, 2019)
Oneiric fiction has been a recurrent topic in children’s and young adult’s literature. Carroll’s model, which is associated to adult literature forms, offered alternative ways to understand human logic through dreams, and it opened up a new world of narrative possibilities, which broke away from moralist realism. Hans Magnus Enzensberger’s novel Where have you been, Robert? can be classified in this tradition. This novel contains seven tales within a story, which includes dream travels, leaps in time, teachings of History and the Arts, and many other components of a bildungsroman. The goal of this paper is, precisely, to analyze the narrative structures of this novel and to pin down their usefulness for a young reader’s learning process and its possible inclusion in the literary corpus for readers over 12.Key words: Dream travel, oneiric fiction, historical novel, time travel, young adult fiction.